2017
DOI: 10.5603/cj.a2017.0030
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral micro-embolization during pulmonary vein isolation: Relation to post-ablation silent cerebral ischemia

Abstract: Background: High incidences of silent cerebral ischemia (SCI) have been revealed by diffusion-weight- DW MRI post-ablation. (Cardiol J 2017; 24, 3: 234-241)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Although not every MES implies cerebral infarction, they have been linked to hyperintense signals on DW-MRI and have been shown to be a predictor of clinical embolic events and stroke. 29,30 TCD monitoring provides a unique opportunity to determine the number and characteristics of MESs present during the different phases of the procedure. 4,28,30,31 This suggests that NSE may be used to detect cerebral injury after ablation, but further evaluation is needed to clarify whether there is a correlation with MRI-detected SCE.…”
Section: Diagnosis and Detection Of Scementioning
confidence: 99%
See 3 more Smart Citations
“…Although not every MES implies cerebral infarction, they have been linked to hyperintense signals on DW-MRI and have been shown to be a predictor of clinical embolic events and stroke. 29,30 TCD monitoring provides a unique opportunity to determine the number and characteristics of MESs present during the different phases of the procedure. 4,28,30,31 This suggests that NSE may be used to detect cerebral injury after ablation, but further evaluation is needed to clarify whether there is a correlation with MRI-detected SCE.…”
Section: Diagnosis and Detection Of Scementioning
confidence: 99%
“…29,30 TCD monitoring provides a unique opportunity to determine the number and characteristics of MESs present during the different phases of the procedure. 4,28,30,31 This suggests that NSE may be used to detect cerebral injury after ablation, but further evaluation is needed to clarify whether there is a correlation with MRI-detected SCE.…”
Section: Diagnosis and Detection Of Scementioning
confidence: 99%
See 2 more Smart Citations
“…Because patients with AF exist in a pre-thromboembolic state, many studies have confirmed that determining the plasma D-dimer level, combined with clinical risk factors, can effectively predict thromboembolic events in NVAF patients [Sadanaga 2010;Erdogan 2014;El Borgi 2015;Kim 2016]. However, a single micro-embolic signal does not necessarily lead to the clinical symptoms of a cerebral embolism [Nagy-Baló 2017].…”
Section: Introductionmentioning
confidence: 99%